Optimization of Machining Parameters on Surface Roughness in EDM of Ti-6AI-4V using Response Surface Method - M. M., Rahman; M. M., Noor; K., Kadirgama; R. A., Bakar; Khan, Md. Ashikur Rahman (2011)
This paper presents the influence of EDM parameters in terms of peak ampere, pulse on time and pulse off time on surface roughness of titanium alloy (Ti-6Al-4V). A mathematical model for surface finish is developed using response surface method (RSM) and optimum machining setting in favor of surface finish are evaluated. Design of experiments (DOE) techniques is implemented. Analysis of variance (ANOVA) has been performed to verify the fit and adequacy of the developed mathematical models. The acquired results yield that the increasing pulse on time causes fine surface till a certain value and then deteriorates the surface finish. It is investigated that about 200 µs pulse off time produce superior surface finish. These results lead to desirable surface roughness and economical industrial machining by optimizing the input parameters.